The impact of political ideology on consumer perceptions of their rights and responsibilities in the sharing economy. (29th June 2020) - Caldwell, Marylouise; Elliot, Steve; Henry, Paul; O'Connor, Marcus
Abstract : Purpose: Despite consumers being essential stakeholders in the exponential growth of the sharing economy, consumers' attitudes towards their rights and responsibilities are relatively unknown. This study aims to test a novel hypothesised model mapping consumers' attitudes towards their consumer rights and responsibilities with that of their political ideology (liberalism, conservatism and libertarianism) and moral foundations (avoiding harm/fairness, in-group/loyalty, authority/respect and purity/sanctity). Design/methodology/approach: Two survey studies were conducted with consumers of the Uber ride share service; the first being to test measures of political ideology and consumer rights/responsibilities. These measures were then taken into the second study along with the Moral Foundations Questionnaire. The hypothesised model was tested using structural equation modelling. Findings: The findings suggest that political ideology associates with similarities and differences in how consumers perceive their rights and responsibilities in the sharing economy, including mutual self-regulation. Support for these findings is established by identifying links with specific moral foundations. Research limitations/implications: This study considers a single participant in the sharing economy.